1987
DOI: 10.1111/j.1600-0447.1987.tb02933.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain glucose metabolism in drug free schizophrenic patients and clinical correlates

Abstract: Regional brain glucose metabolism was investigated in healthy volunteers (n = 10) and in drug free schizophrenic patients (n = 20). The metabolism was determined by positron emission tomography (PET) with 11C-glucose as the tracer. Diagnosis of schizophrenia was made according to RDC and DSM III. Eight patients had their first psychotic episode, four patients had a subchronic course and eight patients had a chronic course with an exacerbation of their illness. Computed tomography (CT) of the brain were made in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0
2

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(43 citation statements)
references
References 32 publications
6
35
0
2
Order By: Relevance
“…From the viewpoint of the model psychosis paradigm, our results are in line with evidence in favor of an association between acute psychotic episodes and hyperactivity in frontal cortical regions (Wiesel et al 1987;Szechtman et al 1988;Cleghorn et al 1989;Ebmeier et al 1993;Parellada et al 1994). These findings are in contrast with the hypofrontality, which has repeatedly been reported in studies with chronic schizophrenic patients (Buchsbaum et al 1982;Farkas et al 1984;Cohen et al 1987;Volkow et al 1987;Weinberger et al 1988;Wolkin et al 1988;Buchsbaum et al 1990;Andreasen et al 1992;Wolkin et al 1992;Siegel et al 1993).…”
Section: Neurometabolic Effects Of the Drugs And Correlations With Pssupporting
confidence: 79%
See 1 more Smart Citation
“…From the viewpoint of the model psychosis paradigm, our results are in line with evidence in favor of an association between acute psychotic episodes and hyperactivity in frontal cortical regions (Wiesel et al 1987;Szechtman et al 1988;Cleghorn et al 1989;Ebmeier et al 1993;Parellada et al 1994). These findings are in contrast with the hypofrontality, which has repeatedly been reported in studies with chronic schizophrenic patients (Buchsbaum et al 1982;Farkas et al 1984;Cohen et al 1987;Volkow et al 1987;Weinberger et al 1988;Wolkin et al 1988;Buchsbaum et al 1990;Andreasen et al 1992;Wolkin et al 1992;Siegel et al 1993).…”
Section: Neurometabolic Effects Of the Drugs And Correlations With Pssupporting
confidence: 79%
“…However, most of these studies were performed with chronically ill patients on various neuroleptic medications, and evidence has accumulated in favor of an association between hypofrontality and negative symptoms (Volkow et al 1987;Wolkin et al 1992). Some few studies with acutely ill patients presenting with positive symptoms failed to demonstrate hypofrontality and did, in part, demonstrate hyperfrontal metabolic patterns (Sheppard et al 1983;Wiesel et al 1987;Cleghorn et al 1989;Ebmeier et al 1993;Parellada et al 1994). Thus, a general link between acute, pharmacologically induced or naturally occurring psychotic states and hyperfrontal metabolic patterns may be hypothesized.…”
mentioning
confidence: 99%
“…However, this is not a consistent finding. In fact, studies in unmedicated acutely relapsed schizophrenics with robust positive symptoms have reported a hyperfrontal metabolic pattern (Volkow et al 1986;Wiesel et al 1987;Cleghorn et al 1989;Ebmeier et al 1993;Parellada et al 1994). The extent to which ketamine administration is an accurate model of brain metabolic changes in schizophrenia needs further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Howe ver, these findi ngs may be due to a biological difference between new-onset and chronic sch izo p hrenia. A recent report by Wiessel and coworkers (43) indicated that duration of illness was directl y correlated with degree ofhypofrontality.…”
Section: Dem Onstration O F Hypofrontality By Petmentioning
confidence: 96%